The Effect Of Cash Turnover And Receivables Turnover On Current Rasio (Study Of Public State-Owned Enterprises Listed On The Indonesia Stock Exchange In 2011-2021) - Nastiti Rizky Shiyammurti; Sri Wulan Sari (Sean Institute, 2024)
This study aims to explore the influence of cash and receivables turnover on current ratio in state-owned companies going public listed on the Indonesia Stock Exchange (IDX) during the period 2011-2021. This research uses a quantitative method with the foundation of positivism philosophy. The population of this study consists of the financial statements of Go Public companies listed on the Indonesia Stock Exchange, with the sample selected using a purposive sampling technique, considering the company's financial position statement and profit and loss statement. Data is collected through financial statement documentation, including cash flow variables and receivables turnover to measure the company's liquidity. Data analysis was performed using multiple linear regression with the help of SPSS software, which included a data description test, a classical assumption test, and a hypothesis test to test the statistical significance of the built model. The results of this study show that cash turnover and receivables turnover have a positive and significant influence on the current ratio of SOEs Going Public on the Indonesia Stock Exchange during the period 2011-2021. At the same time, the cumulative influence of cash and receivables turnover on the current ratio of 47.4% highlights that effective management of these two aspects is crucial in maintaining the company's financial balance in the capital market, emphasizing the importance of cash and receivables management strategies for operational sustainability and financial stability